A SiCN ceramic fiber with rich interface phase and its preparation method and application

By using the precursors containing Si-N main chain and Si-C main chain to form a chemical bonding interface, SiCN ceramic fibers with rich interface phases were prepared, which solved the problem of poor conductivity of existing SiCN ceramic fibers, and achieved the Excellent electromagnetic wave absorption and high temperature stability.

CN116240646BActive Publication Date: 2025-02-11NAT UNIV OF DEFENSE TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310026924.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-09
Publication Date
2025-02-11
Estimated Expiration
2043-01-09

Smart Images

  • Figure CN116240646B_ABST
    Figure CN116240646B_ABST
Patent Text Reader

Abstract

The present invention discloses a SiCN ceramic fiber with rich interface phase and its preparation method and application. The preparation method uses a precursor containing a Si-N main chain and a precursor containing a Si-C main chain as raw materials, and utilizes the similar compatibility characteristics and complementary reaction activities of the two to obtain a two-component precursor polymer with rich interface bonding. The above-mentioned precursor is subjected to the steps of melt spinning, radiation infusibility and high-temperature pyrolysis to prepare a SiCN ceramic fiber with rich interface phase. The two-component precursor used in the preparation method provided by the present invention has low air sensitivity, is easy to simplify the fiber preparation process, and reduces the fiber preparation cost; the rich interface phase can form more polarization loss sites, so that the SiCN fiber has excellent electromagnetic wave absorption performance; the SiCN fiber contains more SiC nano-microcrystalline particles, which can significantly improve the high-temperature stability of the fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of SiCN ceramic fibers, in particular to a SiCN ceramic fiber with rich interface phases and a preparation method and application thereof. Background Art

[0002] The development of high-temperature absorbing ceramic fibers that integrate multiple functions such as "high temperature resistance, load bearing, and wave absorption" is a key bottleneck that needs to be overcome in the development of advanced aerospace stealth equipment. At present, the most common high-temperature absorbing ceramic fibers are SiC fibers, and their long-term use temperature does not exceed 1200°C. At higher temperatures, SiC x O y The significant decomposition of the impurity phase causes a sharp drop in the mechanical properties of the fiber. SiCN ceramic fibers have excellent high temperature resistance, and their composition and structure change only at temperatures above 1400°C. They also have widely adjustable dielectric properties, making them more advantageous than SiC fibers in high temperature wave absorbing applications, and have attracted extensive attention from researchers at home and abroad. However, the conductive components of SiCN ceramic fibers are dominated by Si3N4 and amorphous SiC x N y It is wrapped by insulating components such as aluminum and aluminum, resulting in a smaller leakage current and a smaller contribution to conductivity loss. Summary of the invention

[0003] The present invention provides a SiCN ceramic fiber with rich interface phase and a preparation method and application thereof, which are used to overcome the defects of the SiCN ceramic fiber in the prior art, such as poor electrical conductivity.

[0004] To achieve the above object, the present invention provides a method for preparing SiCN ceramic fiber with rich interface phase, comprising the following steps:

[0005] S1: using a precursor containing a Si-N main chain and a precursor containing a Si-C main chain as raw materials, dissolving the two precursors in an organic solvent, stirring evenly, and obtaining a mixed solution;

[0006] S2: subjecting the mixed solution to a heat reflux treatment under an inert atmosphere to form a chemical bonding interface between the two precursors;

[0007] S3: distilling the mixed solution obtained in step S2 under reduced pressure under heating conditions to obtain a two-component precursor polymer with abundant interfacial bonding;

[0008] S4: melt spinning, radiation infusibility treatment and pyrolysis of the two-component precursor polymer are performed to inherit the interface bonding into the inorganic ceramic to obtain SiCN ceramic fibers with rich interface phases.

[0009] To achieve the above object, the present invention further provides a SiCN ceramic fiber with rich interface phase, which is prepared by the above preparation method.

[0010] To achieve the above objectives, the present invention also proposes an application of SiCN ceramic fiber with rich interface phase, and the SiCN ceramic fiber prepared by the above preparation method or the above SiCN ceramic fiber is used to prepare a high-temperature absorbing structural composite material.

[0011] Compared with the prior art, the present invention has the following beneficial effects:

[0012] The preparation method of SiCN ceramic fiber with rich interface phase provided by the present invention uses a precursor containing a Si-N main chain and a precursor containing a Si-C main chain as raw materials, and utilizes the similar compatibility characteristics and complementary reaction activities of the two to obtain a two-component precursor polymer with rich interface bonding. The above-mentioned precursor is subjected to the steps of melt spinning, radiation inmelting and high-temperature pyrolysis to prepare SiCN ceramic fiber with rich interface phase. The SiCN ceramic fiber prepared by the present invention has rich interface phases, which, on the one hand, come from the pyrolysis inheritance of the interface bonding of the precursor, and on the other hand, come from the interface of SiC microcrystalline particles formed by pyrolysis of the precursor containing the Si-C main chain. Compared with the SiCN fiber preparation method reported before, the preparation method provided by the present invention has the following three major advantages: 1. The two-component precursor used has low air sensitivity, which is easy to simplify the fiber preparation process and reduce the fiber preparation cost; 2. The rich interface phase can form more polarization loss sites, so that the SiCN fiber has excellent electromagnetic wave absorption performance; 3. The SiCN fiber contains more SiC nano-microcrystalline particles, which can significantly improve the high-temperature stability of the fiber. Therefore, the SiCN ceramic fiber prepared by the present invention can be well used in preparing high-temperature wave-absorbing structural composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0014] Figure 1 The relationship curve between the reflection coefficient and the electromagnetic wave frequency of the SiCN ceramic fiber with rich interface phase obtained in Example 1;

[0015] Figure 2 This is a SEM image of the SiCN ceramic fiber with rich interface phase obtained in Example 1;

[0016] Figure 3 This is a SEM image of the SiCN ceramic fiber with rich interfacial phase obtained in Example 2;

[0017] Figure 4 This is a SEM image of the SiCN ceramic fiber with rich interface phase obtained in Example 3;

[0018] Figure 5 This is the SEM image of the SiCN ceramic fiber with rich interface phase obtained in Example 4.

[0019] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] In addition, the technical solutions between the various embodiments of the present invention can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0022] Unless otherwise specified, all drugs / reagents used were commercially available.

[0023] The present invention provides a method for preparing SiCN ceramic fiber with rich interface phase, comprising the following steps:

[0024] S1: using a precursor containing a Si-N main chain and a precursor containing a Si-C main chain as raw materials, dissolving the two precursors in an organic solvent, stirring evenly, and obtaining a mixed solution;

[0025] S2: subjecting the mixed solution to a heat reflux treatment under an inert atmosphere to form a chemical bonding interface between the two precursors;

[0026] S3: distilling the mixed solution obtained in step S2 under reduced pressure under heating conditions to obtain a two-component precursor polymer with abundant interfacial bonding;

[0027] S4: melt spinning, radiation infusibility treatment and pyrolysis of the two-component precursor polymer are performed to inherit the interface bonding into the inorganic ceramic to obtain SiCN ceramic fibers with rich interface phases.

[0028] In order to improve the electromagnetic absorption performance of SiCN ceramic fibers, the present invention provides a general method for in-situ forming a rich interface phase in SiCN fibers. The rich interface phase can effectively increase the polarization loss site, thereby improving the electromagnetic absorption performance of SiCN fibers. The method is based on a Si-N main chain precursor and a Si-C main chain precursor as raw materials, and utilizes the similar compatibility characteristics and complementary reaction activities of the two to obtain a two-component precursor polymer with rich interface bonding. The above-mentioned precursors are subjected to melt spinning, radiation infusibility and high-temperature pyrolysis to prepare SiCN ceramic fibers with rich interface phases. The rich interface phase of SiCN ceramic fibers comes from the pyrolysis inheritance of the precursor interface bonding on the one hand, and from the interface of SiC microcrystalline particles formed by the pyrolysis of the Si-C main chain precursor on the other hand. Compared with the SiCN fiber preparation method reported, the SiCN fiber containing a rich interface phase prepared by the present invention has more excellent electromagnetic absorption performance and high temperature stability.

[0029] Preferably, in step S1, the precursor containing a Si-N main chain is polysilazane or polysilazane; and the precursor containing a Si-C main chain is polycarbosilane.

[0030] Preferably, in step S1, the mass ratio of the precursor containing the Si-N main chain to the precursor containing the Si-C main chain is 5:1 to 1:5.

[0031] Preferably, in step S1, the organic solvent is one of xylene, toluene, tetrahydrofuran and dimethylformamide.

[0032] Preferably, in step S2, the thermal reflow treatment is specifically:

[0033] The mixed solution is heated to 200-300° C. in a reflux device for 1-10 hours to allow chemical bonding to occur between the two precursors to form an interface.

[0034] Preferably, in step S3, the reduced pressure distillation under heating conditions is specifically:

[0035] The mixed solution is heated to the boiling point of the organic solvent, and then evacuated to below 0.01 MPa using a vacuum pump to quickly evaporate the organic solvent in the mixed solution to obtain a two-component precursor polymer with rich interfacial bonding.

[0036] Preferably, in step S4, the melt spinning is specifically:

[0037] The two-component precursor polymer is heated to 10-35°C higher than its softening point in a melt spinning device, and after a degassing treatment for 1-4 hours, it is extruded from a spinning hole under a nitrogen pressure of about 0.4-1.0 MPa, and continuous raw fibers are obtained through a fiber drawing device.

[0038] Preferably, in step S4, the radiation non-melting is specifically:

[0039] The original fibers obtained by melt spinning are placed in an electron beam energy irradiation device with a temperature of 0.5 to 2.5 MeV to achieve infusibility treatment of the original fibers.

[0040] Preferably, in step S4, the pyrolysis is specifically:

[0041] The infusible original fibers obtained after radiation infusibility are placed in a high-temperature pyrolysis furnace, replaced with high-purity nitrogen 2 to 3 times, and then heated to 1000 to 1400°C at a heating rate of 100 to 300°C / hour in a flowing nitrogen atmosphere, kept at the set temperature for 1 to 5 hours, and then cooled with the furnace to obtain SiCN ceramic fibers with rich interface phases.

[0042] The present invention also provides a SiCN ceramic fiber with rich interface phase, which is prepared by the above-mentioned preparation method.

[0043] The present invention also proposes an application of SiCN ceramic fiber with rich interface phase, and the SiCN ceramic fiber prepared by the above preparation method or the above SiCN ceramic fiber is used to prepare a high-temperature absorbing structural composite material.

[0044] Example 1

[0045] This embodiment provides a method for preparing SiCN ceramic fiber with rich interface phase, comprising the following steps:

[0046] (1) dissolving 20 g of polysilazane containing a Si-N main chain and 20 g of polycarbosilane containing a Si-C main chain in 200 ml of xylene, and stirring to obtain a mixed solution;

[0047] (2) subjecting the mixed solution to high temperature reflux treatment under nitrogen atmosphere at a temperature of 200° C. for a period of 1 h, so that the two precursor polymers form a chemical bonding interface and promote uniform mixing of the two precursors;

[0048] (3) heating the mixed solution to the boiling point of the solvent, and then evacuating the mixture to below 0.01 MPa using a vacuum pump to quickly evaporate the solvent of the mixed solution to obtain a two-component precursor polymer with abundant interfacial bonding;

[0049] (4) The precursor polymer is melt-spun to obtain raw fibers, and the raw fibers are irradiated to make them infusible to obtain infusible fibers. The infusible fibers are placed in a high-temperature pyrolysis furnace, replaced twice with high-purity nitrogen, and then heated to 1400°C at a heating rate of 100°C / hour in a flowing nitrogen atmosphere, kept at the set temperature for 1 hour, and then cooled with the furnace to obtain SiCN ceramic fibers with rich interface phases.

[0050] The single-filament tensile strength of the obtained SiCN fiber is 1.9 GPa, and the tensile strength retention rate is 82% after being treated in a nitrogen atmosphere at 1600°C for 1 hour. The minimum reflection coefficient in the electromagnetic wave range of 8-18 GHz is -45 dB, and the effective absorption bandwidth is 3.5 GHz.

[0051] Figure 1 The relationship curve between the reflection coefficient and the electromagnetic wave frequency of the SiCN ceramic fiber with rich interface phase obtained in this embodiment is shown in FIG.

[0052] Figure 2 This is a SEM picture of the SiCN ceramic fiber with rich interface phase obtained in this example. It can be observed from the picture that there are more nanoparticles and more interface components between the particles and the matrix.

[0053] Example 2

[0054] This embodiment provides a method for preparing SiCN ceramic fiber with rich interface phase, comprising the following steps:

[0055] (1) dissolving 20 g of polysilazane containing a Si-N main chain and 60 g of polycarbosilane containing a Si-C main chain in 200 ml of xylene, and stirring to obtain a mixed solution;

[0056] (2) subjecting the mixed solution to high temperature reflux treatment under nitrogen atmosphere at a temperature of 220° C. for a period of 2 h, so that the two precursor polymers form a chemical bonding interface and promote uniform mixing of the two precursors;

[0057] (3) heating the mixed solution to the boiling point of the solvent, and then evacuating the mixture to below 0.01 MPa using a vacuum pump to quickly evaporate the solvent of the mixed solution to obtain a two-component precursor polymer with abundant interfacial bonding;

[0058] (4) The precursor polymer is melt-spun to obtain raw fibers, and the raw fibers are irradiated to make them infusible to obtain infusible fibers. The infusible fibers are placed in a high-temperature pyrolysis furnace, replaced twice with high-purity nitrogen, and then heated to 1300°C at a heating rate of 200°C / hour in a flowing nitrogen atmosphere, kept at the set temperature for 2 hours, and then cooled with the furnace to obtain SiCN ceramic fibers with rich interface phases.

[0059] The single-filament tensile strength of the obtained SiCN fiber is 2.2 GPa, and the tensile strength retention rate is 78% after being treated in a nitrogen atmosphere at 1600°C for 1 hour. The minimum reflection coefficient in the electromagnetic wave range of 8-18 GHz is -33 dB, and the effective absorption bandwidth is 2.9 GHz.

[0060] Figure 3 This is a SEM picture of the SiCN ceramic fiber with rich interface phase obtained in this example. It can be observed from the picture that there are more nanoparticles and more interface components between the particles and the matrix.

[0061] Example 3

[0062] This embodiment provides a method for preparing SiCN ceramic fiber with rich interface phase, comprising the following steps:

[0063] (1) dissolving 100 g of polysilazane containing a Si-N main chain and 20 g of polycarbosilane containing a Si-C main chain in 300 ml of xylene, and stirring to obtain a mixed solution;

[0064] (2) subjecting the mixed solution to high temperature reflux treatment under nitrogen atmosphere at a temperature of 230° C. for a period of 3 h, so that the two precursor polymers form a chemical bonding interface and promote uniform mixing of the two precursors;

[0065] (3) heating the mixed solution to the boiling point of the solvent, and then evacuating the mixture to below 0.01 MPa using a vacuum pump to quickly evaporate the solvent of the mixed solution to obtain a two-component precursor polymer with abundant interfacial bonding;

[0066] (4) The precursor polymer is melt-spun to obtain raw fibers, and the raw fibers are irradiated to make them infusible to obtain infusible fibers. The infusible fibers are placed in a high-temperature pyrolysis furnace, replaced with high-purity nitrogen three times, and then heated to 1200°C at a heating rate of 300°C / hour in a flowing nitrogen atmosphere, kept at the set temperature for 3 hours, and then cooled with the furnace to obtain SiCN ceramic fibers with rich interface phases.

[0067] The single-filament tensile strength of the obtained SiCN fiber is 1.8 GPa, and the tensile strength retention rate is 67% after being treated in a nitrogen atmosphere at 1600°C for 1 hour. The minimum reflection coefficient in the electromagnetic wave range of 8-18 GHz is -26 dB, and the effective absorption bandwidth is 2.3 GHz.

[0068] Figure 4 This is a SEM picture of the SiCN ceramic fiber with rich interface phase obtained in this example. It can be observed from the picture that there are more nanoparticles and more interface components between the particles and the matrix.

[0069] Example 4

[0070] This embodiment provides a method for preparing SiCN ceramic fiber with rich interface phase, comprising the following steps:

[0071] (1) dissolving 20 g of polysilazane containing a Si-N main chain and 100 g of polycarbosilane containing a Si-C main chain in 300 ml of xylene, and stirring to obtain a mixed solution;

[0072] (2) subjecting the mixed solution to high temperature reflux treatment under nitrogen atmosphere at a temperature of 250° C. for a period of 1 h, so that the two precursor polymers form a chemical bonding interface and promote uniform mixing of the two precursors;

[0073] (3) heating the mixed solution to the boiling point of the solvent, and then evacuating the mixture to below 0.01 MPa using a vacuum pump to quickly evaporate the solvent of the mixed solution to obtain a two-component precursor polymer with abundant interfacial bonding;

[0074] (4) The precursor polymer is melt-spun to obtain raw fibers, and the raw fibers are irradiated to make them infusible to obtain infusible fibers. The infusible fibers are placed in a high-temperature pyrolysis furnace, replaced with high-purity nitrogen three times, and then heated to 1400°C at a heating rate of 150°C / hour in a flowing nitrogen atmosphere, kept at the set temperature for 1 hour, and then cooled with the furnace to obtain SiCN ceramic fibers with rich interface phases.

[0075] The single-filament tensile strength of the obtained SiCN fiber is 1.9 GPa, and the tensile strength retention rate is 88% after being treated in a nitrogen atmosphere at 1600°C for 1 hour. The minimum reflection coefficient in the electromagnetic wave range of 8-18 GHz is -43 dB, and the effective absorption bandwidth is 3.8 GHz.

[0076] Figure 5 This is a SEM picture of the SiCN ceramic fiber with rich interface phase obtained in this example. It can be observed from the picture that there are more nanoparticles and more interface components between the particles and the matrix.

[0077] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for preparing SiCN ceramic fiber with rich interface phase, characterized in that: The following steps are involved: S1: using a precursor containing a Si-N main chain and a precursor containing a Si-C main chain as raw materials, dissolving the two precursors in an organic solvent, stirring evenly, and obtaining a mixed solution; S2: subjecting the mixed solution to a heat reflux treatment under an inert atmosphere to form a chemical bonding interface between the two precursors; In step S2, the heat reflux treatment is specifically: heating the mixed solution to 200° C. to 300° C. in a reflux device for 1 to 10 hours, so that chemical bonding occurs between the two precursors to form an interface; S3: distilling the mixed solution obtained in step S2 under reduced pressure under heating conditions to obtain a two-component precursor polymer with abundant interfacial bonding; S4: melt spinning, radiation infusibility treatment and pyrolysis of the two-component precursor polymer are performed to inherit the interface bonding into the inorganic ceramic to obtain SiCN ceramic fibers with rich interface phases.

2. The preparation method according to claim 1, characterized in that In step S1, the precursor containing the Si-N main chain is polysilazane or polysilazane; the precursor containing the Si-C main chain is polycarbosilane.

3. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the precursor containing the Si-N main chain to the precursor containing the Si-C main chain is 5:1 to 1:

5.

4. The preparation method according to claim 1, characterized in that: In step S1, the organic solvent is one of xylene, toluene, tetrahydrofuran and dimethylformamide.

5. The preparation method according to claim 1, characterized in that: In step S3, the reduced pressure distillation under heating conditions is specifically: The mixed solution is heated to the boiling point of the organic solvent, and then evacuated to below 0.01 MPa using a vacuum pump to quickly evaporate the organic solvent in the mixed solution to obtain a two-component precursor polymer with rich interfacial bonding.

6. The preparation method according to claim 1, characterized in that: In step S4, the melt spinning is specifically: The two-component precursor polymer is heated to 10-35°C higher than its softening point in a melt spinning device, and after a degassing treatment for 1-4 hours, it is extruded from a spinning hole under a nitrogen pressure of 0.4-1.0 MPa, and continuous raw fibers are obtained through a fiber drawing device.

7. The preparation method according to claim 1, characterized in that: In step S4, the radiation non-melting is specifically: The original fibers obtained by melt spinning are placed in an electron beam energy irradiation device with a temperature of 0.5 to 2.5 MeV to achieve an infusible treatment of the original fibers.

8. A SiCN ceramic fiber with rich interface phase, characterized in that: The method is prepared according to any one of claims 1 to 7.

9. An application of SiCN ceramic fiber with rich interface phase, characterized in that: The SiCN ceramic fiber prepared by the preparation method according to any one of claims 1 to 7 or the SiCN ceramic fiber according to claim 8 is used to prepare a high-temperature microwave absorbing structural composite material.

Citation Information

Patent Citations

  • Device and method for preparing continuous ceramic fiber through precursor conversion

    CN114790113A